Inhibition of melanogenesis through the deactivation of tyrosinase activity in melanoma cells by labisia pumila fractions - Ware, Ismail (2014)
Effective and safe tyrosinase inhibitors, especially those from natural sources, are desired for the application in food and whitening cosmetic products. In this research, characterization and in-vitro study of L. pumila methanol fractions have been carried out. L. pumila methanol fractions were prepared using solid phase extraction (SPE) and labelled as 40%, 60% and 100% methanol fractions. From characterization by total phenolic content (TPC) analysis, 40% and 100% methanol fractions were found to give the highest amount of phenolic content. The potential tyrosinase inhibition effects of L. pumila methanol fractions were evaluated using B16F1 melanoma cells. The cytotoxicity of the methanol fractions was evaluated using MTT (3-(4, 5-Dimethylthiazol-2-yl)-2,5) diphenyltetrazolium bromide) assay. The results revealed that concentration up to 0.1% w/v of the L. pumila methanol fractions did not affect the cell viability. The secreted melanin had gradually decreased after the treatment with 0.025-0.1% (w/v) of L. pumila methanol fractions. L. pumila methanol fractions for both 40% and 100% methanol fractions had displayed an even stronger inhibitory effect on the secretion of melanin. The effect of melanogenesis on B16F1 indicated that both 40% and 100% methanol fractions had shown a decrease in melanin content between 0.025-0.1% (w/v) concentrations which is better than kojic acid. The melanin content for both 40% and 100% methanol fractions were 64.95 ± 1.87% and 71.91 ± 1.18%, respectively and significantly inhibited the tyrosinase activity in a dose-dependent effect of the L. pumila methanol fractions on the B16F1 melanoma cells. However, the 40% methanol fraction exhibited the highest inhibition up to 73.96 ± 1.58% of tyrosinase activities. Finally, the study indicates that the L. pumila methanol fractions have good potential as the sources of tyrosinase inhibitor.